2022
DOI: 10.3390/joitmc8030120
|View full text |Cite
|
Sign up to set email alerts
|

Continued Intention to Use of M-Banking in Jordan by Integrating UTAUT, TPB, TAM and Service Quality with ML

Abstract: Mobile banking is a service provided by a bank that allows full remote control of customers’ financial data and transactions with a variety of options to serve their needs. With m-banking, the banks can cut down on operational costs whilst maintaining client satisfaction. This research examined the most crucial factors that could predict the Jordanian customer’s continued intention toward the use of m-banking. Following the proposed model, the research was conducted by using a self-conducted questionnaire and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 99 publications
1
13
0
Order By: Relevance
“…Kumar et al [27] discovered that perceived ease of use, perceived usefulness, personal innovation, subjective norms, and trust have a significant impact on mobile banking adoption intention in India. Findings of a recent study on the adoption of mobile banking in Jordan [28] suggest that performance expectancy, effort expectancy, social influence, perceived risk, perceived trust, and service quality are important predictors of behavioral intention, while facilitating conditions turned out to be not significant in that context. Despite the positive trend in the popularity of mobile banking, uptake of mobile banking applications has remained deplorably low, especially in third-world countries [29,30].…”
Section: Adoption Of Mobile Banking Applicationsmentioning
confidence: 88%
“…Kumar et al [27] discovered that perceived ease of use, perceived usefulness, personal innovation, subjective norms, and trust have a significant impact on mobile banking adoption intention in India. Findings of a recent study on the adoption of mobile banking in Jordan [28] suggest that performance expectancy, effort expectancy, social influence, perceived risk, perceived trust, and service quality are important predictors of behavioral intention, while facilitating conditions turned out to be not significant in that context. Despite the positive trend in the popularity of mobile banking, uptake of mobile banking applications has remained deplorably low, especially in third-world countries [29,30].…”
Section: Adoption Of Mobile Banking Applicationsmentioning
confidence: 88%
“…This study used an extended model TAM to study the influence of parents’ anxiety and depression on children’s anxiety and depression when using SNs. The research used CFA, SEM, and five ML methods to validate and verify the findings as in [ 88 , 89 , 90 , 91 ]. The research found that there is a high correlation between parents’ depression and anxiety with children’s depression and a weak correlation with children’s anxiety.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…Prior studies have established that attitude is crucial in shaping one's behavioural intentions in various innovation contexts, such as purchasing from e-commerce retailers Wu, Huang, and Fu (2011): electronic social insurance (Egea & González, 2011) and e-commerce (Beiginia, Besheli, Soluklu, & Ahmadi, 2011;Crespo & Del Bosque, 2010;Grandón, Nasco, & Mykytyn Jr, 2011). The effect of attitude on behavioral intention on m-banking has also been studied by many researchers (Abu-Taieh et al, 2022;Naruetharadhol et al, 2021;Wessels & Drennan, 2010) H8: Attitudes towards using m-banking have a positive effect on behavioral intentions in the use m-banking.…”
Section: Attitude Towards Using M-banking and Behavioral Intentions T...mentioning
confidence: 99%